2003
DOI: 10.1097/01.wcb.0000076701.45782.ef
|View full text |Cite
|
Sign up to set email alerts
|

Persistently Low Extracellular Glucose Correlates with Poor Outcome 6 Months after Human Traumatic Brain Injury despite a Lack of Increased Lactate: A Microdialysis Study

Abstract: Disturbed glucose brain metabolism after brain trauma is reflected by changes in extracellular glucose levels. The authors hypothesized that posttraumatic reductions in extracellular glucose levels are not due to ischemia and are associated with poor outcome. Intracerebral microdialysis, electroencephalography, and measurements of brain tissue oxygen levels and jugular venous oxygen saturation were performed in 30 patients with traumatic brain injury. Levels of glucose, lactate, pyruvate, glutamate, and urea w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
201
2
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(214 citation statements)
references
References 49 publications
4
201
2
6
Order By: Relevance
“…The possibility arises that similar behaviour might explain periodicity of depolarizations in the injured human brain (Dohmen et al, 2008). This has important implications: studies comparing patient outcome with brain microdialysate glucose levels have suggested that periods of low/zero glucose level are linked to poor outcome (Vespa et al, 2003). Although it is not known whether the periods of low glucose levels in these patients were linked to individual PID/CSD events, it seems likely that recurring depolarization events in an injured brain that lead to decreasing glucose levels may compromise clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility arises that similar behaviour might explain periodicity of depolarizations in the injured human brain (Dohmen et al, 2008). This has important implications: studies comparing patient outcome with brain microdialysate glucose levels have suggested that periods of low/zero glucose level are linked to poor outcome (Vespa et al, 2003). Although it is not known whether the periods of low glucose levels in these patients were linked to individual PID/CSD events, it seems likely that recurring depolarization events in an injured brain that lead to decreasing glucose levels may compromise clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in dialysate glucose has been associated (Langemann et al, 1995) and definitively correlated with poor clinical outcome from severe head injury (Vespa et al, 2003), but in most of their patients, the latter group was unable to identify causes for the glucose reductions, since their values for lactate:pyruvate ratio did not suggest ischaemia as a cause of increased (anaerobic) glucose utilisation. Our recent demonstration of ECoG suppressions suggesting CSD or PID events in patients with head injury , the association of transient reductions in dialysate glucose with PIDs in our MCAO experiments, and the associated progressive decline in 'inter-transient' dialysate glucose (Hopwood et al, in press) suggest to us that recurrent depolarisation events in their patients could account for the findings of Vespa and his colleagues.…”
Section: Significance Of Changes In Dialysate Glucosementioning
confidence: 98%
“…The many published reports of assays of brain microdialysate from patients with head injury have until now relied on data from catheters located in cerebral white matter, with dialysate aliquots typically integrated over periods of 60 mins but occasionally over 20 mins (Hutchinson et al, 2002), and assayed most commonly for glucose, lactate, pyruvate, glycerol, and glutamate. Results from brain considered normal provide evidence for local production and consumption of lactate (Abi-Saab et al, 2002) and vary, for example, in their support for a relationship between dialysate lactate (considered in isolation) and outcome in human TBI (Goodman et al, 1999;Vespa et al, 2003). Knowledge of the dynamic nature of perfusion and metabolism in the cerebral cortex in experimental models of traumatic and ischemic brain injury (Katayama et al, 1990;Strong et al, 1996) led us to develop a variant of our existing method for frequent automated assay of glucose and lactate in a continuous dialysate stream, so as to make it suitable for clinical use.…”
Section: Rapid Sampling Of Microdialysate From Peri-lesion Cerebral Cmentioning
confidence: 99%
“…This is of interest in the light of the discussion earlier in this paper of glucose availability and utilisation in the penumbra. In addition, Vespa et al (2003) have recently reported an association of adverse clinical outcome with depletion in microdialysate glucose in patients with severe head injury. The present data also bear some resemblance to the demonstration by of progressive decline in microdialysate glucose associated with recurrent depolarisations in patients with head injury.…”
Section: Selection Of the Marginal Gyrus For Probe Locationmentioning
confidence: 99%
“…The issue of a possible dependence of PID frequency on plasma glucose concentration has taken on new importance for clinical management of acute brain injury, since there is widespread support in general intensive care units for a policy of tight control of plasma glucose with insulin (Van den Berghe et al, 2001). Furthermore, studies of microdialysate glucose concentration in patients with acute brain injury have indicated that depletion of the brain glucose pool carries a poor prognosis (Langemann et al, 1995;Vespa et al, 2003), and there is now good evidence for the occurrence of depolarisation events in the injured brain in many patients (Mayevsky et al, 1996;Strong et al, 2002).…”
Section: Introductionmentioning
confidence: 99%